Enhancing transcranial direct current stimulation via motor imagery and kinesthetic illusion: crossing internal and external tools. Issue 1 (December 2016) - Bodranghien, Florian; Manto, Mario; Lebon, Florent
Abstract Background Transcranial direct current stimulation is a safe technique which is now part of the therapeutic armamentarium for the neuromodulation of motor functions and cognitive operations. It is currently considered that tDCS is an intervention that might promote functional recovery after a lesion in the central nervous system, thus reducing long-term disability and associated socio-economic burden. Discussion A recent study shows that kinesthetic illusion and motor imagery prolong the effects of tDCS on corticospinal excitability, overcoming one of the limitations of this intervention. Conclusion Because changes in excitability anticipate changes in structural plasticity in the CNS, this interesting multi-modal approach might very soon find applications in neurorehabilitation.